Early home literacy and math environment: cross-domain associations between parental literacy and math beliefs - Bosire, Jamlick Peter Ondieki; Palermo, Francisco; Napoli, Amy R. (Frontiers in Psychology, 2025)
We examined how parents’ beliefs are related to home environment practices within and across academic domains (i.e., literacy and math) and the mechanisms through which parents’ beliefs shape home environments. The sample included 945 parents of 0–6-year-old children (M = 4.01, SD = 1.55) from the Early Home Learning Environment dataset. Parents answered questions on beliefs, expectations, perceived appropriateness of activities, math anxiety, and home literacy (HLE) and math (HME) learning environment activities. Using path analysis, we examined the extent to which parents’ beliefs, expectations, perceptions of activity appropriateness, and math anxiety were associated with the HLE and HME; whether expectations for children mediate the associations between parental beliefs and home environments; and whether perceptions of appropriateness of activities and math anxiety moderate the association between parental beliefs, expectations, and home environments. Literacy expectations and perceived appropriateness of literacy activities were positively associated with the HLE, while literacy beliefs and perceptions of appropriateness of literacy activities were associated with the HME. Math beliefs, expectations, and perceptions of appropriateness of math activities were positively associated with the HME, whereas math beliefs, perceptions of appropriateness of math activities, and math anxiety were associated with the HLE. Expectations were only significant within domains and mediated the associations between beliefs and activities for both literacy and math. Only perceptions of appropriateness of math activities moderated the association between math beliefs and HLE. Our study supports the interconnectedness of HLE and HME activities and the importance of parental beliefs in shaping home learning environments.